2014
DOI: 10.1108/md-02-2013-0064
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing, intellectual capital and firm performance

Abstract: Purpose-The aim of this paper is to investigate the impact of knowledge sharing (KS) on firm performance and the mediating role of intellectual capital (IC). Design/methodology/approach-A research model was developed based on prior KS and IC studies. A survey was administered to a sample of high technology firms in China and 228 usable responses were collected. Structural equation modeling (SEM) was employed to test the research model. Findings-Tacit KS significantly was found to contribute to all three compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
446
1
43

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(524 citation statements)
references
References 132 publications
34
446
1
43
Order By: Relevance
“…The premise of relational capital revolves around connecting internal intellectual resources with external stakeholders, hence influencing an organization's ability to create value [76]. According to ([84], p. 517), relational capital (RC) can be defined as "the knowledge that is embedded in the relationships with any stakeholder that affects the firm's life".…”
Section: Relational Capital (Rc)mentioning
confidence: 99%
See 2 more Smart Citations
“…The premise of relational capital revolves around connecting internal intellectual resources with external stakeholders, hence influencing an organization's ability to create value [76]. According to ([84], p. 517), relational capital (RC) can be defined as "the knowledge that is embedded in the relationships with any stakeholder that affects the firm's life".…”
Section: Relational Capital (Rc)mentioning
confidence: 99%
“…According to [80], structural capital (SC) refers to organizational capabilities that are used to meet internal and external challenges. Structural capital can also be defined as the non-human storehouses of knowledge such as organizational culture, routines, data bases, information systems, patents, copyrights, trademarks and so on (see [15] [75] [76]). [81] referred to structural capital as the knowledge that is created and owned by an organization.…”
Section: Structural Capital (Sc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge that is embedded in firm's employees, suppliers, and customers has been term as IC [1], [2]. Previous studies shown that firm's efforts to invest and manage its IC will lead to relatively higher business performance [3], [4]. According to Cahill (2000) [5], 50%-90% of a firm's value is contributed by the efficient management of IC.…”
Section: Introductionmentioning
confidence: 99%
“…IC berpengaruh positif terhadap kinerja keuangan perusahaan -yang merupakan ukuran jangka pendek dan yang paling mudah dilihat, baik pada masa kini maupun di masa yang akan datang. Artinya, IC dapat pula digunakan dalam memprediksi kinerja keuangan perusahaan (lihat misalnya: Chen et al, 2005, Tan et al, 2007Ulum 2008a, Wang 2011, Kamal et al, 2011Ahmad & Mushraf, 2011;Salman et al, 2012;Latif et al, 2012).…”
Section: Pendahuluanunclassified